Phytostabilization of soils contaminated with As, Cd, Cu, Pb and Zn: Physicochemical, toxicological and biological evaluations - R.G. Lacalle; M.P. Bernal; M.J. Álvarez-Robles; R. Clemente (Soil & Environmental Health, 2023)
Phytostabilization of metal-contaminated soils is effective to reduce their solubility and availability in soils and reduce their toxicity to plants. However, the evaluation of appropriate treatments and efficient plant species needs to consider the effects not only of soil characteristics, but also of microbial population. In this work, the effects of seven different plants, including crops and locally adapted species, in two metal-contaminated soils based on a field phytoremediation experiment were evaluated. The two soils (agricultural and mining) contained 6.1, 2322 and 1422, and 13.5, 2071 and 13,971 ​mg ​kg−1 Cd, Pb and Zn concentrations, respectively. In the agricultural soil, combination of crop species Cynara cardunculus and Brassica juncea Czern. was the most effective in reducing metal extractability and in stimulating microbial activity. In the mining soil, compost-assisted phytostabilization decreased CaCl2-extractable Cd and Zn (12–50% for Cd and 71–76% for Zn). The reduced metal toxicity enhanced microbial biomass activity and diversity, particularly under B. juncea. Thus, phytostabilization using selected species was effective in reducing metal toxicity in contaminated soils.